Rasterized Bounding Volume Hierarchies - Novák, Jan; Dachsbacher, Carsten (Computer graphics forum, 2012)
We present the rasterized bounding volume hierarchy (RBVH), a compact data structure that accelerates approximate ray casting of complex meshes and provides adjustable level of detail. During construction, we identify subtrees of BVHs containing surfaces that can be represented by height fields. For these subtrees the conventional ray‐surface intersection, which possibly involves a large number of triangles, is replaced by a simple ray marching procedure to find the intersection with the surface. We describe GPU algorithms for construction, ray casting, and data querying of the RBVH that achieve comparable or higher performance than state of the art acceleration structures for triangle meshes. Moreover, RBVHs provide an inherent surface parameterization for storing data on the surfaces and natively handle triangle and point‐based surface representations. We also show that RBVHs support adaptive level‐of‐detail and can be combined with traditional BVHs to handle complex scenes.